Delusion in death - Robb, J. D., 1950- (New York : Berkley Books, 2013)
When a downtown bar erupts in sudden violence that leaves eighty people dead, Lieutenant Eve Dallas discovers that the bar's patrons were exposed to a lethal cocktail of chemicals and illegal drugs that a sinister killer administered through an airborne method
Includes an excerpt from "Calculated in death", ( p. [359]-373)
Keywords: Dallas, Eve -- (Fictitious character) -- Fiction; Police -- New York (State) -- New York -- Fiction; Policewomen -- Fiction; New York (N.Y.) -- Fiction; Fiction